District heating business models and policy solutions: Financing utilization of low-grade industrial excess heat in the People's Republic of China - Yang Liu; Shan Hu; Brian Dean; Xilong Yao (Asian Development Bank Institute (ADBI), 2020)
The People's Republic of China (PRC) has taken bold actions since 2016 to utilize low-grade industrial excess heat to improve the energy efficiency of district heating systems. This study aims to draw policy insights into the PRC's field experience of overcoming barriers to energy efficiency financing. Firstly, we investigate split incentives, third-party access, and lack of heat resource mapping as key barriers to investing in district heating energy efficiency projects. Second, to enable energy efficiency financing, we analyze three business models: a utility-led model with third-party access, a heat production competition model, and an energy service company model. The business model choice in large part depends on the integration level of production, transmission, and distribution activities in a given district heating system. Third, the heat prices must signal new investments in district heating capacity adequacy. We suggest four options for excess heat pricing, including system cost, free cost, a quantity target for clean heating, and indexing against the next best alternative. Finally, we conclude with policy implications to scale up energy efficiency financing in district heating. Although the analysis is specific for the PRC, the policy and financing issues are global opportunities to improve energy efficiency in district energy systems.
Keywords: Q48; H32; 330; energy efficiency; district energy system; district heating; excess heat